Implementing an Agent-based Multi-Natural Language Anti-Spam Model - Mohammed M.A.; Gunasekaran S.S.; Mostafa S.A.; Mustafa A.; Ghani M.K.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electronic mail; Information filtering; Learning systems; Robotics; Software agents; Visual languages; Anti spam technology; Blocking mechanisms; Business and management; JADE agent platforms; Natural languages; Security and privacy; spam; Visual information; Multi agent systems